STORAGE PROCESSES TO TECHNOLOGICAL CHARACTERISTICS OF COCOD SHELL IMPROVEMENT - O. Z. Mominov; Sh. A. Sulaymanov; Z. E. Erkinov (Bright Mind Publishing, 2025)
The research conducted shows that in recent years, the sericulture industry, including the processes from silkworm farming to the production of silk products, and the equipment used in these processes, have been improving. Currently, to ensure the continuous operation of sericulture enterprises, silkworms are stored in the warehouses of silkworm breeding enterprises.
Keywords: Cocoon, raw silk, linear density, adhesion, sericin, spinning speed, continuous spinning, spinning cycle, raw silk.